Harrison's principles of internal medicine - Fauci, Anthony S (McGraw-Hill, 1998)
Now with a dramatic new emphasis on therapy, Harrison\'s continues to define the practice of medicine into the next millennium. With forty-nine completely new chapters and a complete updating to the entire text, this edition examines the biologic and pathophysiologic origin of disease and charts a clear course for diagnosis and management. And now, the treatment information is expanded and graphically highlighted within the chapter for quick access. Other highlights include an expanded state-of-the-art coverage HIV/AIDS from Drs. Fauci and Lane, a new section devoted to oncology, a revitalized art program, medical ethics, and much more.
Keywords: vnitřní lékařství; Internal Medicine